Editorial: Special Issue on the "Molecular Biology of Disease Vectors" - Kotsyfakis, Michail (International journal of molecular sciences, 2023)
Arthropod disease vectors not only transmit malaria but many other serious diseases, many of which are, to a greater or lesser degree, neglected [...].
Keywords: Animals; Disease Vectors; Humans; Malaria; infekce přenášené vektorem; lidé; Arthropods; členovci; zvířata; Arthropod Vectors; malárie; členovci - vektory; Molecular Biology; molekulární biologie